Faktor FAKTOR-FAKTOR YANG MEMENGARUHI STOCK RETURN - Putra, Jusintri; Syahzuni, Barlia Annis (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
This research aims to determine the factors that influence stock returns in the basic materials sector listed on the Indonesia Stock Exchange (BEI) during the 2020-2022 period. The independent variables used are profitability with Return on Assets (ROA) as a proxy, company size is calculated using the natural logarithm of total assets, liquidity which is proxied by the Cash Ratio, and operating cash flow which is proxied by Operating Cash Flow (OCF). The dependent variable is stock return which is proxied by Capital Gain. The population of this research was 96 companies and a research sample was obtained using a purposive sampling technique of 29 companies for 3 years, resulting in 87 samples. Quantitative methods were used in this research using an explanatory causality design and conducting tests using the SPSS statistical program. The research data has passed the normality test and is suitable for research. Based on the results of the determination test, the variables profitability, company size, liquidity and operating cash flow only 26.1% influence stock returns and it is known that 73.9% of other variables outside research are thought to be able to influence stock returns. The research results stated that the profitability variable had a significant positive effect on stock returns, while the variables company size, liquidity, operating cash flow had no effect on stock returns. This happens because investors are more interested in how much a company can make a profit, so they don't pay too much attention to other variables such as the size of the company, the company's ability to settle short-term obligations or the cash flow that flows into its operating activities.